Hacia una primera investigación comparada de la carrocería en México y Lima al final del virreinato - Álvaro Recio Mir (Nuevo mundo - Mundos Nuevos, 2025)
The knowledge we have of the viceregal carriages, although very embryonic, already allows us to point out provisionally some American peculiarities, in particular, of the capitals of Mexico and Lima. In the same way, a comparative study between them will help to assess their development, as well as point out possible relationships between both production centers. In particular, we will address three questions of the art of carriages: its typologies, uses and its production within the framework of the American guild system.